2021
DOI: 10.1002/aqc.3678
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge surveys with small‐scale fishers indicate challenges to sawfish conservation in southern Papua New Guinea

Abstract: Sawfish (Pristidae) are considered to be among the most threatened families of elasmobranch (sharks and rays). There is a need to gather information on the status of poorly known sawfish populations to assist in global recovery initiatives. This study used interviews with local fishers to investigate the presence of sawfish in southern Papua New Guinea (PNG) and their interactions with and uses and values for small‐scale fishers. A range of sawfish size classes are still encountered throughout southern PNG, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Historically, sawfishes have been observed widely throughout PNG (White et al, 2017a) and these recent observations indicate the contemporary presence of all species. Surveys conducted on local knowledge of sawfishes in PNG's north (Leeney et al, 2018) and south (Grant et al, 2021) coasts further substantiate their contemporary presence in small-scale fisheries, although both studies reported declining catch frequency by local fishers. This indicates that conservation initiatives may be required in PNG to prevent similar trends of regional extinction as seen in other Indo-Pacific nations (Dulvy et al, 2016).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Historically, sawfishes have been observed widely throughout PNG (White et al, 2017a) and these recent observations indicate the contemporary presence of all species. Surveys conducted on local knowledge of sawfishes in PNG's north (Leeney et al, 2018) and south (Grant et al, 2021) coasts further substantiate their contemporary presence in small-scale fisheries, although both studies reported declining catch frequency by local fishers. This indicates that conservation initiatives may be required in PNG to prevent similar trends of regional extinction as seen in other Indo-Pacific nations (Dulvy et al, 2016).…”
Section: Introductionmentioning
confidence: 81%
“…Surveys coincided with the onset of the dry season when most fishing activity occurs (∼September to March), due to safer fishing conditions afforded by calmer whether. Fishers in regions surveyed primarily use gillnets of varied mesh sizes to target croakers (Sciaenidae), barramundi (Lates calcarifer), and elasmobranchs (see Leeney et al, 2018;Grant et al, 2021). With consent from village leaders, local fishermen were invited to present any elasmobranch catch, sawfish rostra, or shark fin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations